How can LVAD support influence ventricular energetics parameters in advanced heart failure patients? A retrospective study. (April 2019) - De Lazzari, Claudio; Capoccia, Massimo; Marconi, Silvia
Abstract: Background and objective: Here we present a retrospective analysis of six heart failure patients previously discussed at a multidisciplinary team meeting. Only three out of six patients underwent LVAD insertion as the most appropriate management option. Methods: We sought to reproduce the baseline conditions of these patients on hospital admission using our cardiovascular software simulator (CARDIOSIM © ). Subsequently, we simulated the effects of LVAD support and drug administration on left and right ventricular energetics parameters. LVAD assistance was delivered by CARDIOSIM © based on the module reproducing the behaviour of the Berlin Heart INCOR pump. Results: The results of our simulations were in agreement with the multidisciplinary team meeting outcome. The analysis of ventricular energetics parameters based on external work and pressure volume area confirmed LVAD support as a beneficial therapeutic option for the three patients considered eligible for this type of treatment. The effects induced by LVAD support and drugs administration showed specific patterns between the two groups of patients. Conclusion: A quantitative approach with the ability to predict outcome during patient's assessment may well be an aid and not a substitute for clinical decision-making.